Agro-food SME clustering: towards an EU legal framework for achieving socio-economic development - Andrikopoulos, Christos (2023)
The business clustering of small and medium-sized enterprises related to the agro-food supply chain (agro-food SME clusters) would be able to contribute significantly to achieving socio-economic development throughout the regions of the European Union. To that end, this thesis discusses the importance of business clustering for SMEs by highlighting relevant legal challenges and arguing for the competitive potential of the agro-food supply chain. It also examines the comparative advantages of high-quality European agro-food goods for the EU and, most importantly, identifies an appropriate EU legal framework in order for the business networks of agro-food SME clusters to operate as commons. By proposing a combined contractual and corporate legal structure for agro-food SME clustering, it argues that SMEs should be connected via contracts with the network centre (cluster organisation) that would operate with a commons approach for the benefit of society and the economy.